# How do you use the product rule to differentiate #y = (x^2 + 2) (x^3 + 4)#?

Applying such concept to your function, we have

Simplifying:

By signing up, you agree to our Terms of Service and Privacy Policy

To use the product rule to differentiate ( y = (x^2 + 2)(x^3 + 4) ), follow these steps:

- Identify the two functions being multiplied: ( f(x) = x^2 + 2 ) and ( g(x) = x^3 + 4 ).
- Apply the product rule, which states that the derivative of the product of two functions is the derivative of the first function times the second function, plus the first function times the derivative of the second function.
- Differentiate each function separately: ( f'(x) = 2x ) and ( g'(x) = 3x^2 ).
- Use the product rule formula: ( (f(x)g(x))' = f'(x)g(x) + f(x)g'(x) ).
- Substitute the derivatives and the original functions into the product rule formula: ( (x^2 + 2)(x^3 + 4)' = (2x)(x^3 + 4) + (x^2 + 2)(3x^2) ).
- Simplify the expression: ( (x^2 + 2)(x^3 + 4)' = 2x^4 + 8x + 3x^4 + 6x^2 ).
- Combine like terms: ( (x^2 + 2)(x^3 + 4)' = 5x^4 + 6x^2 + 8x ).

So, the derivative of ( y = (x^2 + 2)(x^3 + 4) ) is ( 5x^4 + 6x^2 + 8x ).

By signing up, you agree to our Terms of Service and Privacy Policy

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7